2022
DOI: 10.1128/aem.02317-21
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Volatile Organic Compounds from Streptomyces setonii WY228 Control Black Spot Disease of Sweet Potato

Abstract: Black spot disease caused by Ceratocystis fimbriata has caused huge economic losses to worldwide sweet potato production. At present, the control of C. fimbriata mainly depends on toxic fungicides, and there is a lack of effective alternative strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 80 publications
0
29
0
Order By: Relevance
“…These organic compounds travel great distances in structurally heterogeneous environments, as well as in solid, liquid, or gaseous compounds [ 31 ]. VOCs produced by actinomycetes inhibit the growth of phytopathogenic fungi, promote plant growth, possess nematocidal activity, and induce systemic resistance in plants [ 11 , 12 ]. They inhibit the mycelia, causing swelling, conidia collapse, and structural alterations in the fungal cell wall [ 53 ].…”
Section: Main Actinomycete Antagonistic Mechanisms To Phytopathogenic...mentioning
confidence: 99%
See 2 more Smart Citations
“…These organic compounds travel great distances in structurally heterogeneous environments, as well as in solid, liquid, or gaseous compounds [ 31 ]. VOCs produced by actinomycetes inhibit the growth of phytopathogenic fungi, promote plant growth, possess nematocidal activity, and induce systemic resistance in plants [ 11 , 12 ]. They inhibit the mycelia, causing swelling, conidia collapse, and structural alterations in the fungal cell wall [ 53 ].…”
Section: Main Actinomycete Antagonistic Mechanisms To Phytopathogenic...mentioning
confidence: 99%
“…They inhibit the mycelia, causing swelling, conidia collapse, and structural alterations in the fungal cell wall [ 53 ]. The Streptomyces species produces 2-ethyl-5-methylpyrazine and dimethyl disulfide that inhibit mycelial growth and spore germination [ 12 ]. VOCs such as S-methyl ethanethioate, 1,2-dimethyldisulfane, 2-methyl propanoic acid, acetic acid, 3-methyl-butanoic acid, undecan-2-one, nonan-2-one, and 2-isopropyl-5-methylcyclohexan-1-ol have been reported from the actinomycetes Nocardiopsis sp., which inhibit mycelial growth of fungi [ 54 ].…”
Section: Main Actinomycete Antagonistic Mechanisms To Phytopathogenic...mentioning
confidence: 99%
See 1 more Smart Citation
“…NRC50 and NRC51 were able to accumulate prodigiosin-like compounds (red pigments) using agrowaste materials as substrates ( El-Bondkly et al, 2012 ). Some volatile organic products with antifungal activity from Streptomyces setonii WY228 could control black spot disease of sweet potato ( Gong et al, 2022 ).…”
Section: Natural Products From Streptomycesmentioning
confidence: 99%
“…Several studies reported that VOCs produced by Streptomyces sp. have antifungal activity (Wang et al, 2013;Wonglom et al, 2019;Lyu et al, 2020;Ayed et al, 2021;Gong et al, 2022). Sterptomyces alboflavus TD-1 produced 2-methylisorbeneol, which inhibits the growth of A. flavus, A. ochraceus, A. niger and Penicillium citrinum (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%